Comparison of the proliferative and clonogenic growth capacity of wound fluid from breast cancer patients treated with and without intraoperative radiotherapy - Veldwijk, Marlon Romano; Neumaier, Christian; Giordano, Frank Anton; Sütterlin, Marc; Herskind, Carsten; Wenz, Frederik (Translational cancer research, 2015)
The physiological wound healing process after breast-conserving surgery is believed to contribute to a microenvironment promoting motility and invasive activity of residual malignant cells. In intraoperative radiotherapy (IORT), a high single dose of radiation is applied to the tumor bed directly after surgical removal of the tumor and this has been reported to abrogate the stimulatory effects of wound fluid (WF). In the present study, we tested whether IORT alters the influence of WF on the proliferative and clonogenic growth of human MCF7 breast cancer cells. Breast cancer patients were recruited from our IORT studies. WF from 12 patients who underwent IORT, and 18 control patients without IORT, were collected for 24 h. Proliferation was tested in a short-term (MTT) assay and the colony formation assay. A non-significant trend for reduced proliferation was seen in the MTT assay when WF from IORT-treated patients was added at 1% (P=0.07) but not at 3% (P=0.16). No significant effect of IORT-treated WF on the clonogenic growth capacity of MCF7 cells (P=0.79) was found. Our short-term proliferation results with the ER/PgR + -Her2/neu − cell line MCF7 complement previously published data with ER/PgR − -Her2/neu − and ER/PgR − -Her2/neu + breast cancer cell lines showing no significant effect of IORT on short-term proliferation. In addition, for the first time, a lack of an effect of IORT on the clonogenic growth capacity of WF was shown. It should be noted that the present results do not exclude potential other effects of IORT on the cytokine composition and functional activity of WF.